Hand replantation after traumatic amputation in a general surgical hospital - A. N. Plekhanov; V. A. Shagdurov; E. N. Shabaeva; R. D. Garmaev; N. B. Mansheev (Вестник хирургии имени И.И. Грекова, 2019)
The authors described the case of replantation of the right hand in the men of 28 years after a traumatic amputation. This injury was accompanied by damage to the main vessels, which could lead to acute blood loss, hemorrhagic shock and death. The complication after surgery in the form of suppuration of the wound and its effective treatment was shown. This clinical example demonstrated the possibility of limb replantation in traumatic amputations not only in specialized clinics, but also in General surgical hospitals. The basis of the success of the results of the operation was the phasing in the treatment, active monitoring of the replanted limb in order to early identifying possible complications in the postoperative period.